The Effect of Cue Media on Recollections - Hoven, Elise; Eggen, Berry (Human Technology, 2009)
External cognition concerns knowledge that is embedded in our everyday lives and environment. One type of knowledge is memories, recollections of events that occurred in the past. So how do we remember them? One way this can be done is through cuing and reconstructing. These cues can be internal, in our minds, or in our everyday environment. In this paper we look at memory cues in our environment by comparing the effect of cue modality (odor, physical artifact, photo, sound, and video) on the number of memory details people had from a unique one-day real-life event. Contrary to expectation, the no-cue condition (in effect, only a question asking the participants to write down their memories) created on average significantly more memory-details than the cued conditions.